Performance of community health workers under integrated community case management of childhood illnesses in eastern Uganda - Kalyango, Joan N.; Rutebemberwa, Elizeus; Alfven, Tobias; Ssali, Sarah; Peterson, Stefan; Karamagi, Charles (Malaria Journal, 2012)
Curative interventions delivered by community health workers (CHWs) were introduced to increase access to health services for children less than five years and have previously targeted single illnesses. However, CHWs in the integrated community case management of childhood illnesses strategy adopted in Uganda in 2010 will manage multiple illnesses. There is little documentation about the performance of CHWs in the management of multiple illnesses. This study compared the performance of CHWs managing malaria and pneumonia with performance of CHWs managing malaria alone in eastern Uganda and the factors influencing performance.
Keywords: CHW; ICCM; Health system research; Performance; Malaria; Pneumonia; Children; CMDs